Six principles to strengthen qualitative assessments in development interventions. Issue 3 (3rd April 2023) - MacArthur, Jess; Abdel Sattar, Rana; Carrard, Naomi; Kozole, Tyler; Nicoletti, Chris; Riley, Lauren; Roglà, Jennifer; Toeur, Veasna; Willetts, Juliet
ABSTRACT: Qualitative research and evaluation is often described as an art rather than a science. This intangible nature has left many program teams feeling uncertain about how to justify and use qualitative forms of assessment in their monitoring, evaluation, and learning practice. Existing guidance is theoretically based and often focused on applications in the Global North. Building on an expressed need for guidance from a community of practice in Asia and the Pacific, this collaborative action research process aimed to create practical and tested guidance for program teams. The analysis was conducted as part of a Cambodia-based sanitation program assessment. Drawing from literature and the collaborative process, we propose a set of six principles to guide insightful, practical, and robust qualitative assessments. We provide examples regarding how the principles can be used to plan, conduct, and review qualitative assessments with a goal to strengthen the future use of qualitative tools in programming.